2021
DOI: 10.1111/jcal.12623
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis examining the effects of electronic storybooks on language and literacy outcomes for children in grades Pre‐K to grade 2

Abstract: Background: The array of availability of diverse digital reading applications, the mixed results emerging from small-scale experimental studies, as well as the long-standing tradition and range of known positive developmental outcomes gained from adultchild storybook reading warrant an investigation into electronic storybooks (e-books) by performing a meta-analysis, which includes recent studies.Objectives: The overall purpose of this meta-analysis is to examine the impact of e-book reading on language and lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…It is worth noting that the vast majority of studies referred to learning gains in specific subjects. Specifically, several studies examined the impact of digital technologies on students’ literacy skills and reported positive effects on language learning (Balanskat et al, 2006 ; Grgurović et al, 2013 ; Friedel et al, 2013 ; Zheng et al, 2016 ; Chen et al, 2022b ; Savva et al, 2022 ). Also, several studies documented positive effects on specific language learning areas, namely foreign language learning (Kao, 2014 ), writing (Higgins et al, 2012 ; Wen & Walters, 2022 ; Zheng et al, 2016 ), as well as reading and comprehension (Cheung & Slavin, 2011 ; Liao et al, 2007 ; Schwabe et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the vast majority of studies referred to learning gains in specific subjects. Specifically, several studies examined the impact of digital technologies on students’ literacy skills and reported positive effects on language learning (Balanskat et al, 2006 ; Grgurović et al, 2013 ; Friedel et al, 2013 ; Zheng et al, 2016 ; Chen et al, 2022b ; Savva et al, 2022 ). Also, several studies documented positive effects on specific language learning areas, namely foreign language learning (Kao, 2014 ), writing (Higgins et al, 2012 ; Wen & Walters, 2022 ; Zheng et al, 2016 ), as well as reading and comprehension (Cheung & Slavin, 2011 ; Liao et al, 2007 ; Schwabe et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 summarizes the trends identified in current research around the impact of digital technologies on schools’ digital capacity and transformation as found in the present study. Starting as early as 2005, when computers, simulations, and interactive boards were the most commonly applied tools in school interventions (e.g., Eng, 2005 ; Liao et al, 2007 ; Moran et al, 2008 ; Tamim et al, 2011 ), moving towards the use of learning platforms (Jewitt et al, 2011 ), then to the use of mobile devices and digital games (e.g., Tamim et al, 2015 ; Sung et al, 2016 ; Talan et al, 2020 ), as well as e-books (e.g., Savva et al, 2022 ), to the more recent advanced technologies, such as AR and VR applications (e.g., Garzón & Acevedo, 2019 ; Garzón et al, 2020 ; Kalemkuş & Kalemkuş, 2022 ), or robotics and AI (e.g., Su & Yang, 2022 ; Su et al, 2022 ). As this evolution shows, digital technologies are a concept in flux with different affordances and characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Savva et al [43] 2018-2021 73 The results showed that e-book reading improves literacy skills (vocabulary learning).…”
Section: Meta-analysismentioning
confidence: 99%
“…Through picture story books containing STEAM learning, children are invited to formulate and solve problems shown in the storyline. Reading picture story books cannot be separated from the development of EC literacy (Machado, 2015;Saracho & Spodek, 2010;Savva et al, 2022). Various storybook socialization programs and storybook reading methods can build children's literacy early (Beauchat et al, 2009;Ursa & others, 2018;Waldron, 2018).…”
Section: Introductionmentioning
confidence: 99%